Hygrothermal behavior of polybenzimidazole. (14th June 2016) - Liu, Peng; Mullins, Michael; Bremner, Tim; Browne, James A.; Sue, Hung-Jue
Abstract: Poly[2, 2'-( m -phenylene)-5, 5'-bibenzimidazole] (PBI) is used in extremely high temperature harsh environment applications. It is a unique engineering material that is formed into parts by powder-sintering at temperatures as high as 500 °C. Recently, ever increasing demands for high temperature polymers have led to significant interest in PBI such that engineering guidelines could be established for its application in high temperature and highly humid environments. The goal of this work was to understand the material science of PBI in hot-wet environments at temperatures up to 288 °C. Thermal gravimetric analysis and mass spectrometry were employed to identify the degraded volatile products. The molecular scale damping behavior of PBI was probed using dynamic mechanical analysis. The changes in tensile properties and fracture toughness due to environmental exposure were also characterized. Upon heating above 250 °C, moisture-containing PBI exhibits obvious molecular structure change. Evidence of crosslinking and degradation is observed. With 288 °C hot water treatment severe degradation of PBI is observed. Fundamental structure-property relationships of PBI affected by these higher temperature, high moisture content environments are discussed. Graphical abstract: Highlights: The study presents the degradation mechanisms that cause property deterioration of PBI in hot-wet environments up to 288 °C. Structure-property relationships of PBI in high temperature and pressurized aqueous environments are investigated. The findings support that both chain scission and crosslinking occur at high temperatures in the presence of water. Examination of the fracture process reveals the brittle fracture nature of PBI. The embrittlement is caused by hot water induced degradation of PBI molecules.